From colonial ethnology to museum diplomacy. The nationalization of the Museum of Abidjan (Ivory Coast, 1942-1978) - (:unkn) unknown (My University, 2022)
The Ivory Coast Musée des Civilisations, of colonial origin, is historically linked to the program developed by the French Institute of Black Africa (IFAN) starting from the 1940s. The main figure was Bohumil Holas, a French ethnologist of Czech origin, who managed the Museum of Abidjan from 1948 to 1978. Mixing personal strategies and scientific or museumlike programs, he managed to arrange collections with scientific, esthetic, and political values to be used for internal and external political issues: organizing the inventory of ethnicities that form the new independent nation and developing a useful system of museum diplomacy for the Ivorian power. And we should not forget the networks the ethnologist belonged to, which outline other geopolitics of African museums in the age of decolonization.
Keywords: African Research